“It was too much for me”: mental load, mothers, and working from home during the COVID-19 pandemic - Delaney, Caitriona; Bobek, Alicja; Clavero, Sara (Frontiers in Psychology, 2023)
This paper analyses the experiences of working from home (WfH) during the COVID-19 pandemic and the impact it has on working mothers through the lens of "mental load". Remote work, often lauded as a way to reduce work/life conflicts can bring new multifaceted challenges for working mothers and, as this paper shows, suddenly shifting to remote work led to the boundaries between work, care and domestic labour becoming blurred. The data used here are from narrative interviews collected as part of the RESISTIRÉ (RESpondIng to outbreakS through co-creaTIve inclusive equality stRatEgies) Horizon 2020 project, which analyses the impact of COVID-19 policies on gendered inequalities across the EU27 and Türkiye, Serbia, UK and Iceland. We draw on 12 narratives from working mothers in Austria,